2021
DOI: 10.34067/kid.0004522021
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant Polycystic Kidney Disease Prevalence among a Racially Diverse United States Population, 2002 through 2018

Abstract: Among a large racially and ethnically diverse US population, the prevalence of diagnosed ADPKD between 2002 and 2018 was 42.6 per 100,000 persons. ADPKD prevalence (per 100,000) was higher in (non-Hispanic) White (63.2) and Black (73.0) patients compared with Hispanic (39.9) and Asian (48.9) patients. Given the variable penetrance of ADPKD, our findings suggest race may be a factor in the clinical presentation and diagnosis of ADPKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Although the prevalence of ADPKD in the African population is likely to be underdiagnosed, 48 in California, the crude prevalence of ADPKD for Blacks was 73.0, non-Hispanic Whites 63.2, Hispanics 39.9, and Asian/Pacific Islanders 48.9 per 100 000 (p < 0.001). 49 However, our study was not designed to assess the association of this variant with the prevalence of ADPKD in various populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of ADPKD in the African population is likely to be underdiagnosed, 48 in California, the crude prevalence of ADPKD for Blacks was 73.0, non-Hispanic Whites 63.2, Hispanics 39.9, and Asian/Pacific Islanders 48.9 per 100 000 (p < 0.001). 49 However, our study was not designed to assess the association of this variant with the prevalence of ADPKD in various populations.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the KPSC population with ADPKD have been described previously. 22 In brief, we identified all patients who had an ADPKD diagnosis between January 1, 2002 and December 31, 2018 with ≥ 2 ADPKD inpatient and/or outpatient diagnosis codes on separate encounter dates identified by International Classification of Diseases, Ninth and Tenth Revision (ICD-9: 753.12, 753.13; ICD-10: Q61.2, Q61.3) ( Fig 1 ). The second encounter date was defined as the index date.…”
Section: Methodsmentioning
confidence: 99%
“…Reasons why early detection of ADPKD may not occur among Black and Hispanic individuals are unclear. Despite epidemiologic evidence of similar patterns of ADPKD incidence in US studies among racial/ethnic groups (6,7), historical ideologies about racial differences in ADPKD predisposition have implied racial differences in disease patterns and outcomes, potentially leading to race- and ethnicity-based inequities in the detection and evaluation of ADPKD. For instance, a widely cited 1993 New England Journal of Medicine review asserted that “the disease is rare in Africa and less common in American blacks than whites” (8).…”
mentioning
confidence: 99%
“…A recent analysis of USRDS data suggested that Black individuals were less likely than White individuals to have ADPKD listed as the attributing cause for kidney failure overall, but that individuals younger than age 40 with kidney failure attributed to ADPKD were more likely to be Black, suggesting underdiagnosis among older individuals (6). Aung et al (7) Studies are needed to elucidate the role of racial inequities in the treatment of ADPKD, including inequities in the use of renin-angiotensin system inhibitors, which have an essential role in the progression of ADPKD because of the putative role of renin-angiotensin-aldosterone system activation in advancing cyst growth (5). For instance, in a study of patients with ADPKD in California, significantly fewer Hispanic versus White individuals were using angiotensin-converting enzyme inhibitors and angiotensin receptor blockers (7), potentially contributing to inequities in outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation